Application of Hands on Activity Learning Model to Improve English Learning Outcomes of My Uncle is A Zookeeper Material in Grade Viii Students - Kartini Kartini; Nursyamsiah Nursyamsiah; Mualimah Mualimah (International Journal Labs, 2024)
The problems to be studied in this action research are: (a) Does the Hands on Activity Learning Method affect the learning outcomes of Class VIII English? (b) How does the Hands on Activity Learning Method affect the mastery of English learning materials in Class VIII students? The research objectives to be obtained are: (a) To reveal the influence of the Hands on Activity Learning Method on Class VIII English learning outcomes. (b) To reveal the Hands on Activity Learning Method for mastery of Class VIII English learning material. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and reference. The target of this study is Class VIII students. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (69%,), cycle II (76%), cycle III (92%). The conclusion of this study is that the combination of Hands on Activity with working groups can have a positive effect on the achievement and motivation of Grade VIII students, and this learning model can be used as an alternative to English language learning.